2005
DOI: 10.1111/j.1529-8817.2005.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT RESPONSES IN SCYTOSIPHON LOMENTARIA (PHAEOPHYCEAE) INHABITING COPPER‐ENRICHED COASTAL ENVIRONMENTS1

Abstract: Scytosiphon lomentaria (Lingb.) Link. (Phaeophyceae) is one of the two dominant seaweeds in a coastal area of northern Chile affected by copper mine wastes, where the concentration of copper in water and algal tissues remains higher than in nonimpacted sites. Copper-loaded plants develop oxidative stress, as demonstrated by the increased levels of reactive oxygen species and lipoperoxides. This stress was associated with 1) an enhanced activity of the antioxidant enzymes catalase, glutathione peroxidase, ascor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 89 publications
(118 reference statements)
10
62
0
5
Order By: Relevance
“…A number of environmental stressors exert toxic effects via different pathways based on their metabolism and reactivity; metals are reported to exert direct pro-oxidant effects through biochemical oxido/ reduction mechanisms by triggering apoptosis and oxidative stress (Assefa et al, 2005;Valko et al, 2005). Contreras et al (2005) reported a significant increase in ROS and lipo-peroxide levels in seaweeds around the discharges of copper mines, while Bopp et al (2008) reported a 25-to 35-fold ROS induction in rainbow trout gill cells exposed to Cu (total Cu 100 µM, pH 7). Exposure to a mixture of heavy metals (Cu, Cd, Fe and Ni) caused a decrease in the levels of antioxidant enzymes, reduced GSH and an increase in lipid peroxidation in the gills of the freshwater fish Channa punctata (Pandey et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of environmental stressors exert toxic effects via different pathways based on their metabolism and reactivity; metals are reported to exert direct pro-oxidant effects through biochemical oxido/ reduction mechanisms by triggering apoptosis and oxidative stress (Assefa et al, 2005;Valko et al, 2005). Contreras et al (2005) reported a significant increase in ROS and lipo-peroxide levels in seaweeds around the discharges of copper mines, while Bopp et al (2008) reported a 25-to 35-fold ROS induction in rainbow trout gill cells exposed to Cu (total Cu 100 µM, pH 7). Exposure to a mixture of heavy metals (Cu, Cd, Fe and Ni) caused a decrease in the levels of antioxidant enzymes, reduced GSH and an increase in lipid peroxidation in the gills of the freshwater fish Channa punctata (Pandey et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although ROS formation follows a normal physiological process in cellular metabolism, imbalances in generation and removal of ROS species could result in oxidative stress and biological and cellular damage (Dat et al, 2003;Mittler, 2002). ROS formation initiated by the presence of contaminants, resulting in OS, has been reported in biota exposed to pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS can lead to irreversible photooxidative damage, affecting lipid membranes, D1 protein synthesis and thylakoid proteins (Anderson et al, 1997;Niyogi, 1999;Takahashi & Murata, 2008). For example, macroalgae in copper impacted coastal areas of northern Chile have been shown to develop oxidative stress, which can partially be counteracted by rapid and reversible antioxidant activity (Ratkevicius et al, 2003;Contreras et al, 2005). There is evidence that stress proteins (and other biomolecules, see below) located in the cell protect proteins through mechanisms removing ROS, e.g.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…For example, in the coastal zones of northern Chile it has been demonstrated that the high copper levels in the seawater generate in sensitive species a high oxidative stress condition, which appears as the starting point for a series of molecular defense responses. In first place, the condition of oxidative stress has been demonstrated by the direct production of ROS and oxidized lipid in individuals living at an impacted site as well as in those transplanted from control sites to the impacted site (Contreras et al, 2005;Ratckevicius et al, 2003). Compared with high tolerant species such as Ulva and Scytosiphon, in low tolerant species such as L. nigrescens the ROS production by copper, specifically superoxide anions, is poorly attenuated, which is reflected in i) higher levels of oxidized lipids, ii) the generation of cellular alterations and iii) negative effects on early developmental stages of the life cycle (Andrade et al, 2006;Contreras et al, 2007a;.…”
Section: Introductionmentioning
confidence: 99%
“…In macro and micro-algae it is possible to determine that under natural abiotic factors, a common cellular response could involve the over-production of reactive oxygen species (ROS) (Andrade et al, 2006;Contreras et al, 2005Contreras et al, , 2007bContreras et al, , 2009Contreras-Porcia et al, 2011a;Kumar et al, 2010;Lee & Shin, 2003;Liu et al, 2007;Rijstenbil, 2001). ROS are ubiquitous byproducts of oxidative metabolism that are also involved in intracellular signalling processes (e g. Blokhina & Fagerstedt, 2010;Rhee, 2006).…”
Section: Introductionmentioning
confidence: 99%